A functionalized cellulose regenerative microcolumn combined with ultraviolet spectrophotometry for economic detection of selenium in purple potato. Issue 45 (9th November 2016) - Min, Min; Shen, Chen; Fang, Lei; Chang, Yang; Li, Jionghui; Jiang, Yujian; Xiong, Chunhua
Abstract : In this study, a novel separation and preconcentration system, cellulose functionalized by a thioglycolic acid regenerative microcolumn (TGAC), was prepared. Abstract : In this study, a novel separation and preconcentration system, cellulose functionalized by a thioglycolic acid regenerative microcolumn (TGAC), was prepared. Some important parameters affecting the analytical performance of the method such as the amount of the TGAC, enrichment way, pH, initial concentration, flow rate, volume of solution were investigated. Se(iv ) ions can be easily separated from these interference ions using a TGAC microcolumn at pH 3.5. The detection limits for Se(iv ) were found to be 0.53 μg L −1 . In addition, the accuracy of the method was also evaluated by the recovery study and good results were obtained ( P ≥ 98%). The method was applied to the determination of the analytes in purple potato samples such as Ji potato 18, Guang potato 135, jing potato 6, and Ning zi 4, and the Se(iv ) concentrations were found to be in the range of 20.9–52.6 μg kg −1 . 3.0 mol L −1 HCl and 2% KClO3 can elute TGAC-Se(iv ) completely with 0.6 mL min −1, and after five recycling, the regeneration rate of TGAC reached 95.29%, which illustrated that the TGAC column had a good regenerability.